2015
DOI: 10.1007/s11999-015-4442-3
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Positioning and Joint Insufflation Substantially Influence Median and Radial Nerve Locations

Abstract: Background The median and radial nerves are at risk of iatrogenic injury when performing arthroscopic arthrolysis with anterior capsulectomy. Although prior anatomic studies have identified the position of these nerves, little is known about how elbow positioning and joint insufflation might influence nerve locations. Questions/purposes In a cadaver model, we sought to determine whether (1) the locations of the median and radial nerves change with variation of elbow positioning; and whether (2) flexion and joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…These results are supported by several studies reporting the arthroscopic procedure to be effective in patients with posttraumatic elbow contracture [2,[9][10][11][12][13]. However, due to the proximity of neurovascular structures, arthroscopic arthrolysis is a challenging procedure of high technical complexity [4,8]. Therefore, the open procedure is considered by several authors to be the standard treatment for managing contracted elbows, especially in elbows with large intrinsic and extrinsic components [3,6].…”
Section: Arthroskopische Arthrolyse • Offene Arthrolyse • Bewegungsstmentioning
confidence: 76%
“…These results are supported by several studies reporting the arthroscopic procedure to be effective in patients with posttraumatic elbow contracture [2,[9][10][11][12][13]. However, due to the proximity of neurovascular structures, arthroscopic arthrolysis is a challenging procedure of high technical complexity [4,8]. Therefore, the open procedure is considered by several authors to be the standard treatment for managing contracted elbows, especially in elbows with large intrinsic and extrinsic components [3,6].…”
Section: Arthroskopische Arthrolyse • Offene Arthrolyse • Bewegungsstmentioning
confidence: 76%
“…The role of elbow flexion in changing the nerve distances to bony landmarks has been extensively investigated in relation to portal placement for elbow arthroscopy. Hackl et al demonstrated that the distance of the median nerve to the anterior tip of the coronoid and to the anterior border of the trochlea significantly increases from extension to 90° flexion [25]. These findings were supported by a recent review of cadaveric studies, which concluded that the distended elbow in a 90° flexed position minimizes the risk for neurovascular injury with the arthroscope [26].…”
Section: Discussionmentioning
confidence: 91%
“…For the median nerve, reliable landmarks have scarcely been reported, mostly by studies performed in arthroscopic settings and focused on defining anatomical relations at the level of the joint line, without investigating more distal regions. [13,17,18,[25][26][27][28][29]. Nevertheless, knowledge of median nerve position and behavior is essential in complex open surgery and revision cases and constitutes a precious help for all surgeons dealing with medial approaches, especially if lacking in a dedicated subspecialistic training on elbow surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] While advances in arthroscopic techniques have allowed improved access and better treatment of intra-articular pathology, proper patient positioning remains a key component of the procedure (Table 2). Lateral decubitus positioning avoids the potential downsides of prone positioning, including limited airway access, while offering the advantages of access to both the anterior and posterior compartments and the ability for dynamic motion (flexion, extension, pronation, and supination) and intraoperative assessment of all structures 1 (Table 1).…”
Section: Discussionmentioning
confidence: 99%